1995
DOI: 10.1073/pnas.92.16.7177
|View full text |Cite
|
Sign up to set email alerts
|

A chloroplast processing enzyme involved in precursor maturation shares a zinc-binding motif with a recently recognized family of metalloendopeptidases.

Abstract: Nuclear-encoded proteins targeted to the chloroplast are typically synthesized with N-terminal transit peptides which are proteolytically removed upon import.Structurally related proteins of 145 and 143 kDa copurify with a soluble chloroplast processing enzyme (CPE) that cleaves the precursor for the major light-harvesting chlorophyll a/b binding protein and have been implicated in the maturation of the small subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase and acyl carrier protein. The 145-and 143-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 29 publications
2
65
0
Order By: Relevance
“…Sequence Analysis-Although there is probably more than one sort of SPP in plants (20), only one has been cloned (21). This SPP belongs to a family of metalloendopeptidases known as the pitrilysin family (Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence Analysis-Although there is probably more than one sort of SPP in plants (20), only one has been cloned (21). This SPP belongs to a family of metalloendopeptidases known as the pitrilysin family (Ref.…”
Section: Methodsmentioning
confidence: 99%
“…This SPP belongs to a family of metalloendopeptidases known as the pitrilysin family (Ref. 21; peptidase family M16). To determine whether any of the pitrilysin proteins in P. falciparum are homologous to the plant SPPs, a phylogenetic tree of the pitrilysin family was constructed.…”
Section: Methodsmentioning
confidence: 99%
“…We initially demonstrated that a soluble metallopeptidase is responsible for processing of the precursor of light-harvesting chlorophyll a/b-binding protein, and it was implicated in the maturation of the precursors of the ribulose-1,5-bisphosphate carboxylase/oxygenase small subunit and the acyl carrier protein as well (11). We subsequently established that a recombinant form of the enzyme expressed in Escherichia coli cleaved 10 other precursors destined for different compartments and biosynthetic pathways within the organelle, indicating that it is a general stromal processing peptidase (SPP) 1 (12,13). Moreover, we demonstrated that both native SPP and its recombinant form process the precursor of SPP in trans.…”
mentioning
confidence: 99%
“…The C-terminal half is responsible for outer envelope targeting and thought to function as "stop-transfer" sequence to prevent the complete translocation of the protein. After processing by the stromal processing peptidase (SPP) (27), the protein is thought to remain in the intermembrane space (i75). Here it is processed further by an IMS localized type I signal peptidase (28) to its mature form (m75) before it is integrated into the OEM (26,29).…”
mentioning
confidence: 99%